Impact of ZrO2 Content on the Formation of Sr-Enriched Phosphates in Al2O3/ZrO2 Nanocomposites for Bone Tissue Engineering - Nunes, Fabio Caixeta; Santos, Sarah Ingrid Pinto; Colnago, Luiz Alberto; Hammer, Peter [UNESP]; Ferreira, Julieta Adriana; Ambrósio, Carlos Eduardo; Pallone, Eliria Maria Jesus Agnolon (MDPI, 2024)
This study investigates the profound impact of the ZrO2 inclusion volume on the characteristics of Al2O3/ZrO2 nanocomposites, particularly influencing the formation of calcium phosphates on the surface. This research, aimed at advancing tissue engineering, prepared nanocomposites with 5, 10, and 15 vol% ZrO2, subjecting them to chemical surface treatment for enhanced calcium phosphate deposition sites. Biomimetic coating with Sr-enriched simulated body fluid (SBF) further enhanced the bioactivity of nanocomposites. While the ZrO2 concentration heightened the oxygen availability on nanocomposite surfaces, the quantity of Sr-containing phosphate was comparatively less influenced than the formation of calcium phosphate phases. Notably, the coated nanocomposites exhibited a high cell viability and no toxicity, signifying their potential in bone tissue engineering. Overall, these findings contribute to the development of regenerative biomaterials, holding promise for enhancing bone regeneration therapies.
Keywords: alumina-zirconia; biomaterial; calcium phosphates; surface treatment